Impact prediction of translocation of the mitochondrial outer membrane 70 as biomarker in Alzheimer's disease - Cao, Xi; Chen, Yanting; Sang, Xiaoyu; Xu, Shunliang; Xie, Zhaohong; Zhu, Zhengyu; Wang, Ping; Bi, Jianzhong; Xu, Linlin (Frontiers in Aging Neuroscience, 2022)
Mitochondrial dysfunction plays a key role in the pathogenesis of Alzheimer's disease (AD). The translocase of the outer membrane (TOM) complex controls the input of mitochondrial precursor proteins to maintain mitochondrial function under pathophysiological conditions. However, its role in AD development remains unclear. TOM70 is an important translocase present in the TOM complex. In the current study, we found that TOM70 levels were reduced in the peripheral blood and hippocampus of the APP/PS1 mice. In addition, we examined the whole blood mRNA levels of TOM70 in patients with AD, dementia with Lewy bodies (DLB), and post-stroke dementia (PSD). Our study revealed that the mRNA level of TOM70 was decreased in the blood samples of patients with AD, which was also correlated with the progression of clinical stages. Therefore, we proposed that the expression of TOM70 could be a promising biomarker for AD diagnosis and monitoring of disease progression.